Prevalence of Osteoporosis in Patients Undergoing Lumbar Fusion for Lumbar Degenerative Diseases: A Combination of DXA and Hounsfield Units. Issue 7 (1st April 2020) - Zou, Da; Jiang, Shuai; Zhou, Siyu; Sun, Zhuoran; Zhong, Woquan; Du, Guohong; Li, Weishi
Abstract : Study Design: Retrospective analysis. Objective: To investigate the prevalence of osteoporosis (OP) in patients undergoing lumbar fusion for lumbar degenerative diseases (LDD). Summary of Background Data: OP is related to many complications after lumbar fusion for patients with LDD. There are sparse data on the prevalence of OP among this specific population. Moreover, LDD can falsely elevate the bone mineral density measured by dual energy x-ray absorptiometry (DXA), leading to unreliable diagnostic results. Computed tomography (CT) Hounsfield unit (HU) values can help identify osteoporotic patients undetected by DXA. Methods: A total of 479 patients aged≥50 years undergoing lumbar fusion for LDD were reviewed. The diagnosis of OP using DXA was based on World Health Organization criterion. The criterion for OP diagnosed on CT scan was the L1-HU value⩽110. Results: The prevalence of OP diagnosed on lumbar DXA, hip DXA, and both was 32.4%, 19.6%, 39.7%, respectively. The females had higher prevalence of OP diagnosed on DXA (spine and hip) than males (48.9% vs. 27.1%, P  < 0.001). In females but not males, the prevalence of OP significantly increased with age (females, 50–59: 28.0%, 60–69: 58.1%, ≥70: 78.8%, P  < 0.001). Patients having primary diagnosis of degenerative lumbar scoliosis had the higher prevalence of OP than the rest patients (56.5% vs. 36.8%, P  = 0.002). Among the 324 patients diagnosed with non-OP by lumbar DXA, the prevalence of OP diagnosed on CT scan was 25.9%, it increased with age and was also highest in patients with degenerative lumbar scoliosis. Conclusion: OP was quite common among patients aged≥50 years undergoing lumbar fusion for LDD, especially for females aged≥60 years or patients having degenerative lumbar scoliosis. Older patients or patients having degenerative lumbar scoliosis are more likely to have unreliable lumbar T-scores. Measurements of HU values can help identify more osteoporotic patients in this population. Level of Evidence: 3 Abstract : This retrospective study explored the epidemiological characteristics of osteoporosis diagnosed on DXA and CT scan in patients aged≥50 years undergoing lumbar fusion for lumbar degenerative diseases. We identified the patients at high risk of osteoporosis and those who were very likely to have unreliable lumbar T-scores.